2000
DOI: 10.1046/j.1526-4610.2000.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

MMPI‐2 Profiles in Chronic Daily Headache and Their Relationship to Anxiety Levels and Accompanying Symptoms

Abstract: Hysterical traits were observed in a number of patients with chronic daily headache and might constitute a predisposing factor for this condition. With time, the personality profile deteriorates, either through an increase in the hysterical traits or through its transformation, with a parallel increase in anxiety levels and the presence of accompanying symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
5

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 16 publications
1
25
2
5
Order By: Relevance
“…Three-way ANOVA detected main significant effects of group (F [4,225] . Two-way ANOVA did not detect significant differences in impulsive sensation seeking, activity or sociability scores with respect to either group or gender.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-way ANOVA detected main significant effects of group (F [4,225] . Two-way ANOVA did not detect significant differences in impulsive sensation seeking, activity or sociability scores with respect to either group or gender.…”
Section: Resultsmentioning
confidence: 99%
“…1,2]. The results with widely accepted questionnaires like the Minnesota Multiphasic Personality Inventory [3,4], Freiburg Personality Inventory [5], Eysenck Personality Questionnaire [6,7] and Cloninger's seven-factor model of Temperament and Character Inventory [8,9] point to elevated anxiety, neuroticism or harm avoidance in patients with migraine, most of whom do not experience aura. In addition, an increased rate of depression has also been reported in these sufferers [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…Using the MMPI in migraine patients, some authors found normal profiles or, at least, a lower scale elevation than in patients with chronic tensiontype headache or with migraine and tension-type headache superimposed [3,5,6], while others found a marked elevation of several MMPI scales and, in female migraine patients, a typical V configuration of the neurotic triad of the MMPI (with high scores of hypochondria and hysteria and depression score still high but lower than those of the two other scales) [7]. Using the Eysenck personality questionnaire, higher scores of psychoticism were found [13].…”
Section: Discussionmentioning
confidence: 99%
“…Besides autonomic symptoms, a number of other behavioral and somatic symptoms may be observed in women with migraine and when migraine transforms into a chronic daily headache [1][2][3][4][5]. This issue also relates to the problem whether an association exists between personality changes and migraine.…”
Section: Introductionmentioning
confidence: 99%
“…Use of the Zuckerman-Khulman’s or the Eysenck Personality Questionnaire revealed that migraine without aura is characterized by high degrees of neuroticism as well as tension-type headache [6, 26, 27]. Similarly, the Minnesota Multiphasic Personality Inventory showed a personality profile characterized by high scores on the neurotic scale (hypochondria, depression, hysteria) in migraine patients [28]. …”
Section: Introductionmentioning
confidence: 99%